Varietal influence on the nutrient contents and their uptake by wheat - Nipa, FN; Saha, BK; Chowdhury, MAH; Hassan, MN (Journal of the Bangladesh Agricultural University, 2014)
A field experiment was carried out in the Light village of Netrokona Sadar during the period from December 2010 to March 2011 to study the performance of some wheat varieties in terms of nutrient contents and their uptake. The experiment comprised of five varieties of wheat viz. BARI Gam 25, Shatabdi, BARI Gam 26, Prodip and Bijoy. The experiment was laid out in a randomized complete block design with six replications. The nutrient contents and their uptake by wheat grain and straw were significantly influenced by the varieties. The highest N, P, K, S, Ca, B and Zn contents in grain were found in the variety BARI Gam 26 and the lowest N, K, S, Ca and Mg contents were found in the variety Shatabdi. The maximum N, P and S uptake by grain were recorded in the variety BARI Gam 26. On the other hand, the highest K and Zn uptake by grain were obtained from the variety Prodip. The minimum N, K, S, Ca, Mg and Zn uptake by grain were recorded in the variety Shatabdi. In straw, the maximum N, P, K, S, Ca and B uptake were observed in the variety BARI Gam 26 and the minimum N, K, S, Ca and B uptake were found in the variety BARI Gam 25. On the basis of nutrient contents and their uptake, wheat variety BARI Gam 26 showed the best performance. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19898 J. Bangladesh Agril. Univ. 11(2): 221-226, 2013